2022
DOI: 10.3389/fphar.2022.865524
|View full text |Cite
|
Sign up to set email alerts
|

The Function of Metformin in Aging-Related Musculoskeletal Disorders

Abstract: Metformin is a widely accepted first-line hypoglycemic agent in current clinical practice, and it has been applied to the clinic for more than 60 years. Recently, researchers have identified that metformin not only has an efficient capacity to lower glucose but also exerts anti-aging effects by regulating intracellular signaling molecules. With the accelerating aging process and mankind’s desire for a long and healthy life, studies on aging have witnessed an unprecedented boom. Osteoporosis, sarcopenia, degene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 141 publications
0
12
0
Order By: Relevance
“…As for anti-diabetic drugs, the results of previous studies on the beneficial effects of metformin in the treatment of individuals with T2D suggest that metformin may also have therapeutic utility as an anti-aging drug that may also extend lifespan. In detail, metformin is likely to have positive effects on aging and lifespan [ 22 , 23 , 24 , 25 , 26 ] because it has anti-hyperglycemic effects, improves insulin sensitivity, reduces oxidative stress and protects the endothelium and vascular function [ 24 , 27 ]. On the other hand, this study did not show any clinical benefits of using metformin for the extension of lifespan in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…As for anti-diabetic drugs, the results of previous studies on the beneficial effects of metformin in the treatment of individuals with T2D suggest that metformin may also have therapeutic utility as an anti-aging drug that may also extend lifespan. In detail, metformin is likely to have positive effects on aging and lifespan [ 22 , 23 , 24 , 25 , 26 ] because it has anti-hyperglycemic effects, improves insulin sensitivity, reduces oxidative stress and protects the endothelium and vascular function [ 24 , 27 ]. On the other hand, this study did not show any clinical benefits of using metformin for the extension of lifespan in individuals with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very important for diabetic patients to maintain good blood glucose control after surgery to improve the prognosis of patients. Previous articles have showed that drugs, such as metformin not only promote osteoblast proliferation, differentiation, and mineralization, but also inhibit osteoclast production and function thereby increasing bone mineral density and delaying the progression of osteoporosis (16)(17)(18). Therefore, postoperative PKP patients and T2DM can delay or prevent the progression of osteoporosis and prevent postoperative complication development by achieving good blood glucose control.…”
Section: Discussionmentioning
confidence: 99%
“…Even though it was believed that DPP-4 inhibitors, which is a class of antidiabetic drugs, are associated with joint pain, there is evidence stating that people are consuming metformin, another diabetes medication, were lesser to report musculoskeletal pain, including at the back site compared to people that do not consume it (Rai et al, 2019;Carvalho-e-Silva et al, 2021). Metformin could reduce inflammation, counteract oxidative stress and regulate mitochondrial autophagy that could protect chondrocytes from injury (Song et al, 2022). Hence, the role of anti-diabetes medications as an associated factor of LBP remains to be determined.…”
Section: Discussionmentioning
confidence: 99%